2% Crisaborole Ointment for the Treatment of Chronic Cheilitis Caused by Lip Tattoos - Liu X; Liu Q; Guo L; Jiang X (Dove Medical Press, 2024)
Xu Liu,1,* Qingfeng Liu,1,* Linghong Guo,1 Xian Jiang1,2 1Department of Dermatology, West China Hospital, Sichuan University, Chengdu, People's Republic of China; 2Laboratory of Dermatology, Clinical Institute of Inflammation and Immunology, Frontiers Science Center for Disease-Related Molecular Network, West China Hospital, Sichuan University, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Xian Jiang; Linghong Guo, West China Hospital, Sichuan University, #37 Guoxue Alley, Wuhou District, Chengdu, Sichuan, 610041, People's Republic of China, Tel +86-28-85423315, Fax +86-28-85422560, Email jiangxian@scu.edu.cn; linhom.guo@foxmail.comAbstract: The increasing popularity of tattoo art, including facial cosmetic tattoos, has led to a growing societal acceptance of tattoos. However, complications such as lip inflammation following cosmetic lip tattoos remain a concern. This article presents the case of a 47-year-old Asian woman who experienced recurrent lip swelling, purulent discharge, and scarring after receiving lip tattoos. Despite previous treatment with corticosteroid injections yielding unsatisfactory results, the patient showed significant improvement with topical application of 2% Crisaborole, a phosphodiesterase-4 inhibitor. Crisaborole modulates intracellular cyclic adenosine monophosphate levels, thereby reducing tissue inflammation and swelling associated with chronic cheilitis. Additionally, pulse laser therapy was effective in addressing residual tattoo pigment and scar tissue. This case highlights the therapeutic challenges of managing chronic inflammatory diseases of the lips secondary to cosmetic tattoos and introduces Crisaborole as a promising treatment option, offering insights for managing similar conditions in the future.Keywords: lip tattoo, chronic cheilitis, Crisaborole, phosphodiesterase-4 inhibitor, laser therapy